Second-tier strategies in newborn screening: potential and limitations - Gramer, Gwendolyn; Hoffmann, Georg F. (Medizinische Genetik, 2022)
Newborn screening (NBS) is a public health measure to identify children with treatable disorders within the first days of life allowing presymptomatic treatment. It is the most successful measure of secondary medical prevention and part of public health programs in many countries worldwide. Application of second-tier strategies in NBS allows for increased specificity and consecutively a higher positive predictive value. Second-tier strategies can include analysis of specific biomarkers for a target disorder or may be based on molecular genetic analyses. Improving the quality of NBS, for example by second-tier strategies, is of utmost importance to maintain the high acceptance of NBS by families - especially as an increasing number of target disorders is being consecutively included into NBS programs.
Gesehen am 12.07.2022